Effect of magnetic and electric coupling fields on micro- and nano- structure of carbon films in the CVD diamond process and their electron field emission property. (7th March 2018) - Wang, Yijia; Li, Jiaxin; Hu, Naixiu; Jiang, Yunlu; Wei, Qiuping; Yu, Zhiming; Long, Hangyu; Zhu, Hekang; Xie, Youneng; Ma, Li; Lin, Cheng-Te; Su, Weitao
Abstract: In this paper, both electric field and magnetic field were used to assist the hot filament chemical vapor deposition (HFCVD) and we systematically investigated the effects of which on the (1) phase composition, (2) grain size, (3) thickness and (4) preferred orientation of diamond films through SEM, Raman and XRD. The application of magnetic field in electric field, so called 'the magnetic and electric coupling fields', enhanced the graphitization and refinement of diamond crystals, slowed down the decrease of film thickness along with the increase of bias current, and suppressed diamond (100) orientation. During the deposition process, the electric field provided additional energy to HFCVD system and generated large number of energetic particles which might annihilate at the substrate and lose kinetic energy, while the Lorentz force, provided by magnetic field, could constrict charged particles (including electrons) to do spiral movement, which prolonged their moving path and life, thus the system energy increased. With the graphitization of diamond films intensified, the preferred orientation of diamond films completely evolved from (110) to (100), until the orientation and diamond phase disappeared, which can be attributed to (I) the distribution and concentration ratio of carbon precursors (C2 H2 and CH3 ) and (II) graphitization sequence of diamond crystal facets. Since the electron field emission property of carbon film is sensitive to the phase composition, thickness and preferred orientation, nano- carbon cones, prepared by the negative bias current of 20 mA and magnetic field strength of 80 Gauss, exhibited the lowest turn-on field of 6.1 V −1 μ m −1 .